ESTIMATES OF GENETIC PARAMETERS AND CORRELATIONS BETWEEN MORPHOLOGICAL TRAITS IN SOYBEAN GENOTYPES - Leite, Wallace de Sousa [UNESP]; Pavan, Bruno Ettore [UNESP]; Aires Matos Filho, Carlos Humberto; Feitosa, Fabiano Soares; Oliveira, Cleidismar Barbosa de (Univ Federal Mato Grosso, 2015)
This study aimed to estimate genetic parameters and correlations between traits of agronomic interest in a soybean population, to select traits for use in crop breeding. Thus, we analyzed 28 soybean genotypes in randomized block design with three replications. We evaluated the following agronomic traits: plant height at flowering (HPF) and maturity (HPM), pod insertion height (HIP), grain yield (GY), number of nodes (NN) and number of pods (NP). There was a significant effect of genotypes on all traits, indicating the existence of genetic variability, with great possibility of obtaining genetic gain for all characters. The highest estimate of the genetic variation coefficient was obtained for GY, which also showed coefficient between CVg/CVe above 1, indicating favorable condition for the selection of this trait. There were positive and significant genetic correlations at 1% probability for HPM with characters HPF, HIP, GY, NN and NP. These findings showed that this population has the genetic variability and potential for improvement for all traits, and grain yield in gain can be obtained especially for genotypes with greater plant height at maturity.
Keywords: Glycine max; genetic variability; genetic correlations; grain yield